Depletion Layer Modeling for Short Gate Length Non-Uniformly Doped GaAs MESFET Under Dark and Illuminated Condition (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
This paper presents an analytical expression for the depletion region height of short gate length GaAs MESFET with non-uniform doping profile in the channel region. Both, dark as well as illuminated conditions have been considered for model formulation. Depletion region height sensitivities on the doping parameters have also been demonstrated.
Keywords: Depletion region; GaAs MESFET; Illumination; Non-uniform doping